Współczesne dylematy jakości żywności - Gabryšová, Marie (Contemporary Dillemas of Food Quality, 2005)
The EU countries are obliged to observe regulations which aim is to protect safety and quality of food for all participants of the common market. Insufficient knowledge about so called modem methods of improvement of food (GMO and irradiation of food) is able to cause a significant problem in the area of quality of life.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 224-230